The levels of Community Involvement in Health (CIH): a case of rural and urban communities in KwaZulu-Natal - G.G. Mchunu (AOSIS, 2009)
The study aimed to describe the practice of community involvement in health programmes.The study therefore explored the nature and practice of community involvementin health programmes in the two communities in KwaZulu Natal. Thestudy was guided by the conceptual framework adapted from Amstein's,( 1969) Ladderof Citizen Participation. This framework shows different levels and steps in communityparticipation. A case study method was used to conduct the study. The twocases were one urban based and one rural based community health centers in theIlembe health district, in Kwa Zulu Natal. A sample of 31 persons participated in thestudy. The sample comprised 8 registered nurses, 2 enrolled nurses 13 communitymembers and 8 community health workers. Data was collected using structured individualinterviews and focus group interviews, and was guided by the case protocol.Community involvement in health largely depended on the type of community, withrural community members being in charge of their health projects and urban communitymembers helping each other as neighbours in times of need.